Strategic process in the field of communication and information technologies. A competitive approach in regulated industries - Acevedo Borrego, Adolfo (2014)
This article is derived from research on planning in the communications industry and information technology, it presents strategic process in a business context of economic success, which poor strategic vision. During final of last century was the technological breakthrough and structural change in the industrial organization of the telecommunications industry, with important economic performance and increasing volume of service even with sustained degradation customer service. It argues that technological dynamics finds no counterpart sector in improving the quality of service, as it continues to focus on profitable markets. Supranational efforts, such as the information society incorporating criteria such as digital gap, are attempts to guide sectoral.